ENTREPRENEURIAL MINDFULNESS AND AMBIDEXTROUS LEADERSHIP IN STRENGTHENING RESILIENCE: THE MEDIATING ROLE OF SCALING-UP PERFORMANCE CAPACITY IN INDONESIAN FAMILY BUSINESSES - Patricia, Patricia; Alvaro Pratama (Milestone: Journal of Strategic Management, 2025)
Entrepreneurial resilience is crucial for the sustainability of family businesses, especially in dynamic and uncertain environments. Despite the growing interest in entrepreneurial resilience, existing research has yet to fully explore how both cognitive (entrepreneurial mindfulness) and strategic (ambidextrous leadership) leadership factors collectively shape resilience, particularly in the family business context. This study addresses this gap by investigating how scaling-up performance capacity mediates these relationships, providing a more integrative perspective on resilience-building mechanisms in family firms. Using a quantitative approach, data was collected through questionnaires from 265 family business owners in Indonesia. The data was analyzed utilizing Smart PLS (Partial Least Squares Structural Equation Modeling) to evaluate the proposed hypotheses. The results reveal that entrepreneurial mindfulness and ambidextrous leadership have a positive and significant impact on entrepreneurial resilience. Furthermore, the capacity for scaling-up performance functions as an important mediator, enhancing the connection between leadership behaviors and resilience. Theoretically, this study contributes to the expanding literature on family business sustainability by integrating resilience-building strategies with leadership and performance capacity constructs. These findings provide practical contributions for family businesses in adopting effective leadership strategies and increasing adaptive capacity to enhance resilience against market uncertainties and generational transitions.